Activity and the density of rheumatologists in Russian Federation, 2013-2017 - I. M. Son; M. A. Ivanova; T. A. Sokolovskaya; V. V. Liutsko; L. I. Dezhurny (Кардиоваскулярная терапия и профилактика, 2019)
The incidence of noncommunicable diseases is one of the problems for the health of the population. In this regard, an adequate supply of rheumatologists and other specialists is necessary for timely providing medical care to the population.Aim. To analyze the current state of the provision of rheumatologists and their activities in the Russian Federation.Material and methods. Used data of Federal statistical observation over the period from 2013 to 2017, the paper used statistical, analytical, descriptive methods of statistics.Results. This article presents an analysis of the data of official statistics on the rheumatologists’ density. The results indicate the stability of the situation in this specialty, although in general there was a decrease in the staffing of outpatient clinics.Conclusion. Study showed a decrease in specialists staffing and stable situation on the density of outpatient departments of medical organizations.